Records of U.S. Chief of Counsel for War Crimes, Nuremberg Military Tribunals, re Nazi industrialists (NARA ;, 1976)
"The Nazi industrialist documents collected or created by the office, U.S. Chief of Counsel for War Crimes, concern German industry and finance, including the Flick, I.G. Farben and Krupp concerns. The collection comprises the original or photostatic copies of records ... and includes translations, interrogations and depositions."